Regeneration Patterns of Tree Species Along an Elevational Gradient in the Garhwal Himalaya - Chandra Mohan Sharma; Ashish Kumar Mishra; Om Prakash Tiwari; Ram Krishan; Yashwant Singh Rana (Mountain Research and Development, 2018)
This study assessed the regeneration status of tree species at different elevations in Himalayan forests. For this purpose, we assessed the densities of seedlings, saplings, and adult trees of various forest-forming species to understand their population structure and regeneration patterns. Five elevational ranges—<2000, 2000–2500, 2500–3000, 3000–3500, and >3500 m above sea level—were selected in various ranges in the Bhagirathi River catchment area in the Garhwal Himalaya. The highest species richness was recorded at the lowest elevational range, and the lowest species richness was recorded at the highest elevational range. Species diversity, measured using the Simpson and Shannon–Wiener diversity indices, was highest at the lowest elevations and lowest at the highest elevations. Abies spectabilis, Cedrus deodara, Rhododendron arboreum, Pinus roxburghii, and Quercus oblongata were dominant and widely adapted with appropriate regeneration potential at various elevations, whereas Aesculus indica, Juglans regia, and Sorbus cuspidata showed less ability to regenerate, indicating a threat to their survival in the near future. Tree species of subalpine forests Abies pindrow, A. spectabilis, Acer acuminatum, Betula utilis, and R. arboreum were observed to expand their upper limits into alpine meadows. Weak regeneration by some dominant tree species, and expansion by a few less-dominant or even rare species, indicate likely future compositional changes in Himalayan forests.